What's done in the dark will be brought to the light: effects of influencer transparency on product efficacy and purchase intentions. Issue 5 (11th January 2020) - Woodroof, Parker J.; Howie, Katharine M.; Syrdal, Holly A.; VanMeter, Rebecca
Abstract : Purpose: The purpose of this paper is to examine the impact of the type of disclosure used by social media influencers on consumer evaluations of influencer transparency, product performance expectations and how those factors ultimately influence purchase intentions. Design/methodology/approach: An experiment was conducted with 321 participants recruited from MTurk to test a moderated serial-mediation model. Findings: The results indicate that when consumers become cognizant that an influencer's branded promotional post may have been motivated by an underlying financial relationship, they evaluate the influencer as significantly less transparent if a more ambiguous disclosure is used relative to a clearer disclosure. Transparency perceptions of the influencer impact consumers' perceptions of product efficacy as well as purchase intentions. Originality/value: Social media influencers are rapidly emerging as a popular marketing tool for brand managers, but consumer response to this form of promotion is not well understood. To the best of the authors' knowledge, this is the first study to investigate how the type of endorsement disclosure used by a social media influencer impacts consumer perception of influencer transparency, product efficacy and purchase intentions. Further, this research demonstrates the applicability of the persuasion knowledge model in the domain of influencer marketing.